2005
DOI: 10.1073/pnas.0406085102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mouse SLC39A8 as the transporter responsible for cadmium-induced toxicity in the testis

Abstract: Testicular necrosis is a sensitive endpoint for cadmium (Cd 2؉ , Cd) toxicity across all species tested. Resistance to Cd-induced testicular damage is a recessive trait assigned to the Cdm locus on mouse chromosome 3. We first narrowed the Cdm-gene-containing region to 880 kb. SNP analysis of this region from two sensitive and two resistant inbred strains demonstrated a 400-kb haplotype block consistent with the Cd-induced toxicity phenotype; in this region is the Slc39a8 gene encoding a member of the solute-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
238
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(245 citation statements)
references
References 64 publications
6
238
1
Order By: Relevance
“…The protective effect of Zn may be due to interaction with Cd in the testis itself, where uptake of the two metals across endothelial cells occurs to gain access to the parenchyma. Earlier studies utilizing genetic approaches have shed light on the role of Zn transporters, such as zinc-iron related transporter proteins (ZIP8), in the uptake of Cd to the testis [52]. Moreover, Liu et al [53] demonstrated that Zn was the best inhibitor of ZIP8-mediated Cd uptake into cells and reported that this influx increased under condition of hypozincemia.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of Zn may be due to interaction with Cd in the testis itself, where uptake of the two metals across endothelial cells occurs to gain access to the parenchyma. Earlier studies utilizing genetic approaches have shed light on the role of Zn transporters, such as zinc-iron related transporter proteins (ZIP8), in the uptake of Cd to the testis [52]. Moreover, Liu et al [53] demonstrated that Zn was the best inhibitor of ZIP8-mediated Cd uptake into cells and reported that this influx increased under condition of hypozincemia.…”
Section: Discussionmentioning
confidence: 99%
“…Single-dose inhalation of cadmium chloride (0.1%) in rats results in an acute increase of the GSSG/GSH ratio in cell-free BAL fluid, thereby indicating enhanced oxidative stress. Repeated inhalation of cadmium chloride (1 h per day for 3-5 weeks) also results in a progressive increase of GSH in the cell-free BAL fluid [8,[45][46][47][48][49][50]. Notably, the enzymatic activity of major antioxidants, including superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase, is altered in response to cadmium exposure [51][52][53].…”
Section: Molecular and Cellular Targets Of Cadmiummentioning
confidence: 99%
“…They also suggest that at least in certain rodent strains, MT may not be the principle cadmium binding protein in the testes and may not play a major role protecting testicular cells from cadmiuminduced toxicity. Several other cadmium transporters present in the testes have recently been identified including ZIP8 and tesmin, which contains an MTlike motif [Dalton et al 2005;He et al 2009;Martin et al 2007;Sugihara et al 1999]. These transporters may play more prominent roles in testicular metal binding.…”
Section: Gene Polymorphisms: Potential Gene-environment Interactionsmentioning
confidence: 99%